Implementation of Introduction to Education and Evaluation of the Learning Process among Students of STKIP Tomakaka Tiwikrama - Gusnawati H (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to describe the implementation of Introduction to Education and the evaluation of the learning process among students of STKIP Tomakaka Tiwikrama. Introduction to Education is a fundamental course that provides students with an understanding of the meaning, objectives, functions, and components of education as a systematic process. In the learning process, evaluation plays an important role in measuring student achievement, identifying learning difficulties, and improving the quality of teaching and learning activities. This study uses a descriptive qualitative approach by examining the implementation of learning activities, evaluation techniques, and the challenges faced by lecturers and students. The results show that the evaluation of the learning process is carried out through various assessment techniques, including written tests, oral tests, assignments, observation, and class participation. Evaluation is not only used to determine student learning outcomes but also serves as feedback for improving teaching strategies, learning materials, and classroom management. Therefore, the implementation of Introduction to Education and learning process evaluation at STKIP Tomakaka Tiwikrama is expected to strengthen students’ pedagogical understanding and improve the quality of future educational practices